Alcohol Use and Depression: A Mendelian Randomization Study From China - Zhu, Chen; Chen, Qihui; Si, Wei; Li, Yingxiang; Chen, Gang; Zhao, Qiran (Frontiers in Genetics, 2020)
Background: Alcohol use has been linked to a number of physical conditions, but the relationship between alcohol drinking and depression, one of the most common mental disorders that is a significant contributor to the global burden of disease, is still under debate. We aim to help fill the literature gap on the causal effect of alcohol use on depression by using genetic instruments of ALDH2 rs671 and ADH1B rs1229984 in the Mendelian randomization (MR) framework. Materials and methods: We collected a sample of 476 middle-aged and older adults from mainland China. The 10-item Center for Epidemiologic Studies Depression Scale (CESD-10) was used to measure the status of depression. The frequency and intensity of alcohol consumption were measured by (1) a binary indicator of drinking or not; (2) the total number of drinking occasions during the past 30 days; and (3) the weekly ethanol consumption in grams. Results: MR estimates indicated that alcohol use was causally associated with a lower risk of depression. Parameter estimates of drinking or not [b=-0.127, p=0.048], number of drinking occasions [b=-0.012, p=0.040], and weekly ethanol consumption [b=-0.001, p=0.039] were all negative and statistically significant. The results were robust after adjustments for potential confounders (e.g., income, smoking, parental drinking behaviors), and the exclusion of heavy or former drinkers. Conclusions: This is one of the first studies to investigate the causal relationship between alcohol use and mental health using an MR design in East Asian populations. Further studies are needed to clarify the mechanisms of this causal link.